1989
DOI: 10.1105/tpc.1.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation by a circadian rhythm.

Abstract: Transcription of genes encoding the light-harvesting chlorophyll a/b protein (Cab) was shown previously to be regulated by light and a number of developmental factors. ! show that a circadian rhythm in transcriptional activity is superimposed on these other regulatory programs. In vitro transcription measurements in isolated maize leaf nuclei demonstrated that changes in transcription are not coincident with light-dark transitions and that diurnal changes in transcription continue in continuous light and disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…The outlying peak during the continuous dark period may be an anomally. However, erratic fluctuations and somewhat higher levels of psbA expression during dark phases have also been found in tomato (16 (19). Our study showed that diurnal fluctuations of the steady-state cab mRNA in Douglas-fir were relatively minor and the fluctuations that occurred did not appear to be highly influenced by factors associated with photoperiodicity.…”
Section: Expression Of Cab and Psba Genes In Douglas-firmentioning
confidence: 64%
“…The outlying peak during the continuous dark period may be an anomally. However, erratic fluctuations and somewhat higher levels of psbA expression during dark phases have also been found in tomato (16 (19). Our study showed that diurnal fluctuations of the steady-state cab mRNA in Douglas-fir were relatively minor and the fluctuations that occurred did not appear to be highly influenced by factors associated with photoperiodicity.…”
Section: Expression Of Cab and Psba Genes In Douglas-firmentioning
confidence: 64%
“…In the majority of studies of circadian-regulated gene expression in plants, light rather than darkness is the extemal signal influencing the amplitude of cycling mRNA levels (Guilano et al, 1988;Taylor, 1989). Indeed, darkness was observed to have a negative effect on the amplitude (Guilano et al, 1988) and transcriptional regulation of expression (Taylor, 1989) of Cab genes in tomato and maize, respectively.…”
Section: Ldentification Of Mrnas Associated With Photoperiodicmentioning
confidence: 99%
“…Recently, it has been recognized that circadian rhythms regulate expression of a number of light-regulated plant genes, notably nuclear-encoded photosynthetic genes, and in certain cases, this regulation occurs at the leve1 of gene transcription (Kloppstech, 1985;Piechulla and Gruissem, 1987;Guilano et al, 1988;Nagy et al, 1988;Piechulla, 1988;Meyer et al, 1989;Taylor, 1989;Millar and Kay, 1991). Phase shifting by red light or temperature of the circadian rhythm of cycling mRNA levels has also been reported, strongly suggesting control of gene expression by the biological clock (Tavladoraki et al, 1989;Piechulla and Riesselmann, 1990).…”
mentioning
confidence: 99%
“…Those which have been studied extensively include the rhythms of carbon dioxide metabolism in the succulent plant Bryophyllum fedtschenkoi {Wilkins, 1959{Wilkins, , 1983{Wilkins, , 1989{Wilkins, , 1991, of luminescence in the photosynthetic, armoured, marine dinoflagellate Gonyaulax polyedra (Sweeney, 1971;Johnson & Hastings, 1986;Roenneberg, Colfax & Hastings, 1989;Morse, Fritz & Hastings, 1990), of leaf movement in the runner bean Phaseolus multiflorus (coccineus) (Biinning, 1973), Albizza julibrissin and Sanianea saman (Satter & Galston, 1981 ;Satter et al, 1988), of conidiation in the fungus Neurospora crassa (Sargent, Briggs & Woodward, 1966;Feldman, Gardner & Denison, 1979;Techel ei al., 1990), and of photosynthetic capacity in the alga Acetabularia mediterranaea (Sweeney & Haxo, 1961 ;Sweeney, TofBi & Rubin, 1967;Schweiger & Schweiger, 1977;Schweiger, Hartwig & Schweiger, 1986). A number of recent studies report a rhythm in the synthesis of the chlorophyll alb pigment-protein complex of photosystem H in a wide variety of plants (Taylor, 1989). Circadian rhythms also occur in animals as diverse as the fruit fly (Drosophila), lizards (Lacerta), hamsters (Mesocricetus) and man (Bunning, 1973;Brady, 1982).…”
Section: Occurrence Of Circadian Rhythmsmentioning
confidence: 99%
“…LTnder light/dark conditions the level of nitrate reductase gene expression shows a diurnal rhythm in tomato and tobacco, but it has not yei: been established whether this rhythm is circadian and persists in constant environmental conditions. Taylor (1989) has shown that transcription of genes coding for the lightharvesting Chi a/b apoprotein exhibits circadian rhythmicity which is superimposed on other regulatory mechanisms in Zea mays. The rhythm was monitored through in vitro transcription in isolated maize leaf nuclei, and it persisted in continuous light but not in darkness.…”
Section: Organismsmentioning
confidence: 99%